Registros de Thraupis episcopus (Linnaeus, 1766) en la ciudad de Chilpancingo, Guerrero, México - Castro-Torreblanca, Marisol; Blancas-Calva, Epifanio (Instituto de Ecología, A.C., 2018)
We recorded the presence of two individuals of the Blue-gray Tanager (Thraupis episcopus) on an urban area in Chilpancingo city in the state of Guerrero. These records are important because increases in 250 km the known southwest limit of the distribution of the species.